Preselection algorithm based on predictive control for direct matrix converter - Dan, Hanbing; Zhu, Qi; Peng, Tao; Yao, Sun; Wheeler, Patrick (Institution of Engineering and Technology, 2017)
This paper presents an enhanced predictive control strategy to reduce the calculation effort for direct matrix converters. The main idea is to preselect the switching states to decrease the calculation effort during each sample period. The proposed preselection algorithm enables a predefined cost function to consider only the preselected switching states to perform the expected control. On the basis of the preselection of switching states at each sample period, the proposed method can effectively reduce the calculation effort as well as show a good performance. The proposed predictive control scheme using only preselected switching states needed to generate the desired source/load current waveforms and control the input power factor. The feasibility of the proposed method is experimentally verified and results are presented in the paper.